RESPONSIBILITIES OF BUSINESS ACTORS ON FOOD SANITATION REVIEWED FROM CONSUMER PROTECTION LAW - Khifni kafa Rufaida (International Journal of Law Reconstruction, 2018)
The purpose of this research is to overcome the awareness problem of business actor, especially street vendors and consumer on the importance of hygiene and food sanitation, to identify how big the responsibility of business actors (Street Vendors) to products sold under the UUPK. This research is also a form of Research Grant for Beginner Lecturers, which was expected to direct and nurture the ability to research novice lecturers, and become a training tool for novice lecturers to publish their research results in accredited scientific journals, both locally and nationally. The results showed that the level of awareness of business actors on food sold is still lacking, it is also supported by the lack of consumer awareness of the importance of protection of consumers. The form of responsibility of business actors (street vendors) is to provide compensation to the disadvantaged consumers under Article of the Protection Act of Consumers.